Beclomethasone dipropionate dry-powder inhalation compared with conventional aerosol in chronic asthma. Issue 6138 (2nd September 1978) - Carmichael, J; Duncan, D; Crompton, G K
Abstract : In a double-blind study beclomethasone dipropionate inhaled as a dry powder in doses of 100 microgram four times daily and 150 microgram four times daily was compared with the conventional aerosol dose of 100 microgram four times daily in 20 outpatients with chronic asthma. Each of the three treatments was given for four weeks. The dry powder in a dose of 150 microgram four times daily had advantages over the other two treatments in terms of FEV1 and the number of exacerbations of asthma during the study. There were no adverse reactions to inhaling dry-powder beclomethasone. It was concluded that this new way of administering the drug was effective in chronic asthma, and should allow most patients with chronic asthma who cannot use conventional pressurised aerosols efficiently to benefit from inhaled corticosteroid treatment.